Ten Year Experience of Radioiodine Dosimetry: is it Useful in the Management of Metastatic Differentiated Thyroid Cancer?. Issue 5 (May 2017) - Sun, F.; Gerrard, G.E.; Roberts, J.K.; Telford, T.; Namini, S.; Waller, M.; Flux, G.; Gill, V.M.
Abstract: Aims: When a fixed activity of radioiodine is given for differentiated thyroid cancer (DTC), absorbed doses of radioiodine can vary widely and are not usually measured. Leeds Cancer Centre has routinely used a form of lesion-specific dosimetry for radioiodine patients. This study investigated if the results of dosimetry influenced treatment decisions for patients with advanced DTC. Materials and methods: Since 2005, patients with regionally advanced/metastatic DTC, who underwent radioiodine treatment together with dosimetry, were included in this study. Patients were excluded if their radioiodine post-treatment scan showed no abnormal uptake. Dosimetry was calculated using images taken 2, 3 and 7 days post-radioiodine. Regions of interest were drawn around lesions that required dosimetry and a time–dose activity curve was created. The total cumulative activity was equal to the area under the curve. Each patient's results were prospectively assessed by their oncologist regarding the usefulness of dosimetry in making management decisions. Results: Thirty patients were studied and underwent 102 admissions of radioiodine between them. Dosimetry was carried out during 83 of 102 admissions. An absorbed dose of >20 Gy was taken as significant from dosimetry calculations, following which further radioiodine was considered. In 80% of patients, dosimetry was found to be useful when making treatment decisions. Only on 1/19 admissions did dosimetry calculate a minimum dose above 20 Gy in patients who had a total of four or more admissions for radioiodine. Ten per cent (3/30) had a complete response to radioiodine, both biochemically and radiologically, with a median follow-up of 6.7 months. Thirty-three per cent had a partial response/stable disease to radioiodine. The remainder had progressive disease. The decision to discontinue radioiodine therapy was often based on dosimetry and thyroglobulin results. Dosimetry was very useful for patients with thyroglobulin antibodies. Conclusion: Only 10% had a complete response. Therefore, a significant number of patients became refractory to radioiodine during a course of repeat admissions for treatment. Dosimetry (often together with thyroglobulin and anatomical scans) helped to identify these patients to avoid further futile radioiodine therapy. Highlights: Absorbed doses from radioiodine treatments vary widely. In Leeds, UK, lesion-based dosimetry for radioiodine has been used for >10 years. Radioiodine dosimetry was useful in 80% of patients and affected decision making. The decision to discontinue radioiodine often based on dosimetry.